Determinants of Preference for and Consumption of Liquid Milk by Indian Households - M, UMANATH; K, Vijayasarathy; B N, Pradeepa Babu (Indian Journal of Dairy Science, 2016)
Abstract The present study aims at analysing the impact of household characteristics on the preference for and consumption quantity of liquid milk. Food expenditure data, gathered by National Sample Survey Organisation (NSSO), Government of India, was used for the analysis. Since around 25 per cent of the total respondents had been observed as the zero consumers of liquid milk, Heckman sample selection model was employed to estimate the impact of household characteristics on preference and consumption of liquid milk. The results of the study reveal that price of liquid milk, per capita income, home production of milk and presence of refrigerators in a household have a significant positive influence on both preference and consumption of liquid milk, whereas the practice of having food away from home has a negative impact on the consumption of liquid milk. Also, both consumption quantity and probability of consuming the liquid milk among Indian households differed considerably across income groups and locations of residents. The results of the study are expected to be helpful to the policy makers, producers, processors and traders of milk and milk products.